Learner Errors In Descriptive Text Made By Eight Grade Students Of SMP N 2 Colomadu In 2013/2014 Academic Year - Yuniati, Kristina Fitria, Prof. Dr. Endang Fauziati, M. Hum, Dr. Dwi Haryanti, M.Hum (2014)
This study aims to describe the learner errors made by the eight grade students of SMP N 2 Colomadu in their composition of writing descriptive text; identifies the types of lexical errors, syntactical errors, and discourse errors; explains the frequency of each type of errors; describes the dominant type of errors; and identifies the source of errors. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation technique. There are some steps in collecting data, namely: the writer gets the data from the teacher, the writer reads every text made by the students accurately, the writer giving marks in erroneous sentences, the writer writes again all the erroneous sentences of the student's composition in a list and it become a data. In analyzing data, the writer uses Dulay, Burt and Krashen classification of errors theory, Slamet theory for the frequency of each type of error, and Brown, Norrish, Richard are source of error theories. The result of the research shows that the eight grade students of SMP N 2 Colomadu still make 162 errors in their compositions. The writer finds that from 162 data, there are three classification of error based on the combination of linguistic category taxonomy and surface strategy taxonomy. They are lexical error consist of 32,7% which cover: wrong spelling 28,39%, false friends 1,23%, and use Indonesia word/code switching 3,08%. Errors in syntactical consist of 52,41% which cover: bound morpheme (-S) 16,63 %, BE 35,78 %, misordering 11,72 %, article 1,85 %. Errors on discourse consist of 14,81 % which cover of component of discourse in reference 8,64% and conjunction 6,17 %. The writer also finds 2 dominant source of errors, namely: interlingual transfer and intralingual transfer. So, the students in SMP N 2 Colomadu especially eight grade class C make many error in their composition on descriptive text. The dominant error is lexical error especially in wrong spelling and grammatical construction